2012
DOI: 10.1007/s00228-012-1331-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety of ginger use in pregnancy: results from a large population-based cohort study

Abstract: Use of ginger during pregnancy does not seem to increase the risk of congenital malformations, stillbirth/perinatal death, preterm birth, low birth weight, or low Apgar score. This finding is clinically important for health care professionals giving advice to pregnant women with NPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…The use of ginger during pregnancy was not associated with any increased risk of congenital malformation (adjusted OR 0.8, 95% CI 0.5-1.4) or with any of the other pregnancy outcomes investigated (i.e. preterm birth and low birth weight, adjusted risk estimates ranging from 0.7 to 1.0) compared to women who had not been exposed (41).…”
Section: Herbal Remediesmentioning
confidence: 79%
See 1 more Smart Citation
“…The use of ginger during pregnancy was not associated with any increased risk of congenital malformation (adjusted OR 0.8, 95% CI 0.5-1.4) or with any of the other pregnancy outcomes investigated (i.e. preterm birth and low birth weight, adjusted risk estimates ranging from 0.7 to 1.0) compared to women who had not been exposed (41).…”
Section: Herbal Remediesmentioning
confidence: 79%
“…In the first study, 1,020 (1.5%) women reported using ginger (most commonly against nausea) during pregnancy (41). The use of ginger during pregnancy was not associated with any increased risk of congenital malformation (adjusted OR 0.8, 95% CI 0.5-1.4) or with any of the other pregnancy outcomes investigated (i.e.…”
Section: Herbal Remediesmentioning
confidence: 98%
“…The plants used in this study have been shown to be safe to use up to doses as large as 1gram [38][39][40][41] . Giving such high doses chronically may however have dire consequences.…”
Section: Discussionmentioning
confidence: 92%
“…All pregnant women presenting with nausea in the pharmacy should be counselled on diet and life style changes and on the supplements listed in the national guidelines on treatment of nausea in pregnancy (e.g. ginger supplements, which have evidence based safety and usefulness in relief of the symptoms) (Heitmann, 2013).…”
Section: Discussionmentioning
confidence: 99%